Socio-Demographic and Perpetrators Experience in Committing Crime: A Descriptive Study on Male Young Offenders Undergoing Community Service Order - Tharshini, A/P Sivabalan; Fauziah, Ibrahim; Ezarina, Binti Zakaria; Mohd Suhaimi, Bin Mohamad (Penerbit Akademia Baru, 2016)
The present study attempts to identify the underlying socio-demographic and perpetrators experience in committing crime among male young offenders undergoing community service order. An observational cross-sectional approach was applied using self-administered survey among young offenders. A total number of 60 respondents were recruited from Malaysia Department of Social Welfare to participate in this study. For this research, the sample criteria are male young offenders aged between 18 to 21 years old. Written and signed consent form were also given to the respondents to obtain their agreement prior to their voluntary participation in the research. The self-administered survey consisted of two main sections. Section one contained questions on socio-demographic of the young offenders while section two queried information regarding type of crimes, weapon usage, factors associate to commit crime, factors contributing for successfully executing criminal acts, factors associates to failure in committing crime and how they were caught. Data were compiled, organised and analysed using SPSS version 23.0. Results indicates that despite living with their family, young person involves in crime acts. This study suggest to examine family factors that contribute to the perpetrator experience to involve in crime in Malaysia.